Addressing prosthetic joint infections via gentamicin-eluting UHMWPE spacer. (June 2020) - Gil, Dmitry; Atici, Ali E.; Connolly, Rachel L.; Hugard, Shannon; Shuvaev, Sergey; Wannomae, Keith K.; Oral, Ebru; Muratoglu, Orhun K.
Abstract : Aims: We propose a state-of-the-art temporary spacer, consisting of a cobalt-chrome (CoCr) femoral component and a gentamicin-eluting ultra-high molecular weight polyethylene (UHMWPE) tibial insert, which can provide therapeutic delivery of gentamicin, while retaining excellent mechanical properties. The proposed implant is designed to replace conventional spacers made from bone cement. Methods: Gentamicin-loaded UHMWPE was prepared using phase-separated compression moulding, and its drug elution kinetics, antibacterial, mechanical, and wear properties were compared with those of conventional gentamicin-loaded bone cement. Results: Gentamicin-loaded UHMWPE tibial components not only eradicated planktonic Staphylococcus aureus, but also prevented colonization of both femoral and tibial components. The proposed spacer possesses far superior mechanical and wear properties when compared with conventional bone cement spacers. Conclusion: The proposed gentamicin-eluting UHMWPE spacer can provide antibacterial efficacy comparable with currently used bone cement spacers, while overcoming their drawbacks. The novel spacer proposed here has the potential to drastically reduce complications associated with currently used bone cement spacers and substantially improve patients' quality of life during the treatment. Cite this article: Bone Joint J 2020;102-B(6 Supple A):151–157.